Scopes and horizons of the home world - Kolinko, Maryna (Skhid, 2015)
The paper deals with spatial interconnection of home world and political worlds. Тhe author pays special attention to the methodological and theoretical approach of such thinkers as E. Husserl, which has a heuristic value for the research of the phenomenon of life-word. Semantics of dividing the social space into "my" and "somebody else's" employs Husserl phenomenological historicity type interpretation. Differences in domestic and alien world formation are analyzed. The correlation of the dynamics of cultural changes to the behaviour of the subject, when anomie and the gap of values' connection of a new culture with human's value orientations are seen as the strain basics of life, is shown. The way of life of the individual, without traditions' support is comprehended. Every cultural group is formed on foundation of steady cultural matrix. Symmetry of cultural distinctions within the framework of the "paternal field" gives basis for understanding, moves apart scopes and extends horizons of the home world. The dialogue is viewed as a productive strategy of tolerant communication. Identity studying (phenomenon of boundaries, formation of identities) is necessary for understanding of peculiarities of the dialogue of cultures in the conditions of political conflict.